Using the laws of logarithms:
log10 [ 100a^(3)b^(-2/1) ÷ b^(2) ]
= log10 [100a^(3) b^(-2/1) ] - log10 [b^(2)]
= log10 [100] + log10 [a^(3)] - 2 log10 [b] - log10 [b^(2)]
= 2 + 3x - 2y - 2
= 3x - 2y
If log10 a=x and log10 b=y, express log10 [ 100a^(3)b^(-2/1) ÷ b^(2) ] in terms of x and y
3 answers
2+3x - (5/2 y)
We can write the given expression as:
2 + 3x - (5/2)y
Or,
2 + 3x - 2.5y
Thus, the expression 2+3x - (5/2 y) simplified is 2 + 3x - 2.5y.
2 + 3x - (5/2)y
Or,
2 + 3x - 2.5y
Thus, the expression 2+3x - (5/2 y) simplified is 2 + 3x - 2.5y.